Dampak pendidikan karakter kedalam moralitas remaja di era digital saat ini - prasetyo, prayogi (Maliki Interdisciplinary Journal, 2024)
The rapidly developing digital era has brought significant changes in behavior and social interactions, particularly among adolescents. Technological advancements have impacted their morality, making it increasingly complex due to the negative influences of the vast digital world. This research aims to examine the influence of character education on the morality of teenagers in the digital age. The method used is qualitative, employing a literature review approach to analyze this influence. Character education is not only the responsibility of schools but also of society, especially parents. They need to monitor their children's use of electronic devices and provide guidance and boundaries. In this way, character education becomes a crucial foundation for preparing to face moral challenges in today's digital era.